Peran Empowering Leadership Style dalam Meningkatkan Kepuasan Kerja Pegawai pada Organisasi Pemerintah - Tito - Yassin; Hasyim Hasyim (Benefit: Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to determine the effect of empowering leadership style on employee job satisfaction mediated by psychological capital, psychological well-being, and employee work engagement in government organizations. The study draws on survey data with 129 respondents from employees in Indonesia government agency. Confirmatory factor analysis was conducted to examine the convergent validity of the construct measures. Partial least square (PLS) Algorithm was used to estimate the fit of the hypothesized model to the data. The research found that empowering leadership has a significant effect on the psychological capital, work engagement, and psychological well-being of employees. The role of employee psychology capital has a positive influence on the relationship between empowering leadership styles with psychological well-being and employee work engagement. The results of this study also found that the role of employee psychological capital mediation did not significantly influence the relationship between empowering leadership style and employee job satisfaction, but the role mediation of psychological well-being and work engagement became a good mediating variable on the relationship between empowering leadership style and job satisfaction. The results of this research are expected to be useful academically and managerially for government organizations in Indonesia.